Polyimide hot-melt prepreg, composite material and preparation method of polyimide hot-melt prepreg and composite material

Through improved dissolution and concentration processes and double-layer impregnation gradient prepreg technology, the problems of uneven distribution of resin content and difficulty in volatile control in polyimide thermosetting composite materials are solved, and the polyimide hot melt prepreg is realized efficient preparation and excellent mechanical properties of composite materials.

CN119463248AActive Publication Date: 2025-02-18AEROSPACE INST OF ADVANCED MATERIALS & PROCESSING TECH

Patent Information

Application Number
CN202411483992.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-23
Publication Date
2025-02-18
Estimated Expiration
2044-10-23

AI Technical Summary

Technical Problem

In the preparation of polyimide thermosetting composite materials, the prior art faces challenges such as uneven resin content distribution, difficulty in controlling volatile content and environmental pollution. In particular, the insoluble and non-melting properties of fully imidized polyimide resins reduce the fibers. Wetting efficiency affects the viscosity and storage stability of the prepreg.

Method used

Using an improved dissolution and concentration process scheme, the composite temperature and pressure of imidized resin matrix and reinforced fiber are adjusted through double-layer impregnation gradient prepreg technology to achieve gradient distribution of the viscosity and solid content of the resin system on the prepreg cross-section. .

Benefits of technology

The resin content of the polyimide hot melt prepreg is controlled and the adhesion is good, which reduces the porosity and manufacturing cost of the composite material, and improves the comprehensive mechanical properties of the composite material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119463248A_ABST
    Figure CN119463248A_ABST
Patent Text Reader

Abstract

The invention discloses a polyimide hot-melt prepreg, a composite material and a preparation method of the polyimide hot-melt prepreg and the composite material, and belongs to the technical field of composite materials. The preparation method comprises the following steps: preparing a polyimide resin solution for impregnating fibers and self-adhering a surface layer from polyimide, a single solvent and a mixed solvent; preparing semi-solid polyimide prepreg for fiber impregnation and surface layer self-adhesion based on the two polyimide resin solutions, and then preparing an adhesive film and sequentially compounding with fiber cloth to obtain a fiber prepreg; and preparing the polyimide hot-melt prepreg based on the fiber prepreg. According to the preparation method disclosed by the invention, the reinforced fibers are fully infiltrated, and then the toughened and tackified resin layer is compounded on the surfaces of the impregnated reinforced fibers, so that the polyimide hot-melt prepreg with controllable resin content and good paving adhesiveness is obtained, and therefore, the low-porosity high-quality fiber reinforced composite material is prepared, the control difficulty of a forming process is greatly reduced, and the production efficiency is improved. The production efficiency is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a polyimide hot-melt prepreg, a composite material and a preparation method thereof, and belongs to the technical field of composite materials. Background Art

[0002] Polyimide is a type of high-performance heat-resistant polymer material with imide ring as the core structural unit. Its unique molecular design gives it excellent heat resistance and can work stably under extreme conditions. The maximum heat resistance can reach 600°C and it can be used for a long time in the temperature range of 200-500°C. In particular, thermosetting polyimide, by constructing a body network structure, exhibits extremely high heat resistance, excellent mechanical strength and excellent dielectric properties. These characteristics occupy a pivotal position in the field of advanced composite materials. As a matrix, this type of material is widely used in high-performance engine cold end components, thermal protection structures of cutting-edge strategic defense systems, and key components of cruise and tactical missiles in the aerospace field, demonstrating its irreplaceable application value.

[0003] At present, the preparation paths of high-temperature resistant polyimide resin-based composite materials are mainly divided into two methods: one is to use the PMR (polymer mesophase resin) method, which first prepares an imide oligomer solution containing active end groups, and then performs imidization cross-linking in the laminate structure to form the final network structure. However, this process has a violent imidization reaction, accompanied by the release of small molecules, complex process control, and is prone to problems such as fiber morphology buckling and increased porosity; at the same time, unreacted monomers and solvent residues shorten the storage stability of the material and limit the efficiency of large-scale production. The other is the imidization soluble resin method, which completes the imidization at the beginning of resin synthesis, and the resulting oligomer has good solubility and is convenient for subsequent processing. This method avoids the additional imidization step in the curing process of the composite material, improves production efficiency, reduces porosity, and realizes long-term stable storage of the material. However, in practical applications, if the solution impregnation method is used to prepare prepregs, it still faces challenges such as uneven distribution of resin content, difficulty in controlling volatiles, and environmental pollution.

[0004] To overcome the above difficulties, the hot melt adhesive film method has become the preferred solution for large-scale preparation of prepregs due to its ability to accurately control the resin content and volatile matter. However, for fully imidized polyimide resins, its insoluble and infusible properties significantly reduce the fiber impregnation efficiency, and the strict control of the solid content of the adhesive film affects the viscosity and storage stability of the prepreg, thereby restricting the balance between the draping process and the control of volatile matter, becoming a key technical bottleneck that needs to be solved in this field. At present, systematic improvement research on this issue is still insufficient, and it is urgent to explore new solutions to promote the widespread application of imidized polyimide resins in the field of high-end composite materials. Summary of the invention

[0005] The purpose of the present invention is to overcome the deficiencies of the prior art and provide a polyimide hot-melt prepreg, a composite material and a preparation method thereof.

[0006] To achieve the above purpose, the technical solution adopted by the present invention is as follows:

[0007] In a first aspect, the present invention provides a method for preparing a polyimide hot-melt prepreg, the steps of which include:

[0008] 1) mechanically stirring polyimide and a single solvent to obtain a polyimide resin solution for impregnating fibers;

[0009] 2) mechanically stirring the polyimide and the mixed solvent to obtain a polyimide resin solution for the self-adhesive surface layer;

[0010] 3) performing reduced pressure distillation on the two polyimide resin solutions obtained in steps 1) and 2) to obtain a semi-solid polyimide prepreg for impregnating the fiber and for surface self-adhesion;

[0011] 4) placing the semi-solid polyimide prepreg for impregnating the fiber in a hot melt three-roller machine for hot melting, coating the prepreg on a release paper to obtain an impregnated fiber resin film, and compounding the impregnated fiber resin film with a fiber cloth through multiple hot pressing rollers to obtain an impregnated fiber prepreg;

[0012] 5) placing the semi-solid polyimide prepreg for the self-adhesive surface layer in a hot melt three-roller machine for hot melting, and coating it on a release paper to obtain a self-adhesive surface resin film; the self-adhesive surface resin film is double-sidedly laminated with the fiber cloth impregnated with the fiber prepreg obtained in step 4) through multiple hot pressing rollers to obtain a fiber prepreg;

[0013] 6) The fiber prepreg obtained in step 5) is processed by a heating plate, a hot pressing roller, and a cooling plate, the upper release paper is peeled off and covered with a PE film to obtain a polyimide hot-melt prepreg.

[0014] Furthermore, the polyimide in steps 1) and 2) is an acetylene-terminated, allyl norbornene-terminated or phenylacetylene-terminated polyimide resin, specifically one or more of NPI-550, NPI-550-2, KH-360A / B, PMR-15, PMR-Ⅱ-50, PETI-5, LARC-160, LARC-13, etc.

[0015] Furthermore, in step 1), the single solvent is selected from one of N,N-dimethylacetamide (DMAC), dimethylformamide (DMF), and N-methylpyrrolidone (NMP).

[0016] Furthermore, in step 2), the mixed solvent comprises a low boiling point solvent and a high boiling point solvent, the low boiling point solvent is selected from one or more of dioxane, n-butanol, isopropanol, cyclopentanone, and sec-butanol, and the high boiling point solvent is selected from one or more of N,N-dimethylformamide, N,N-dimethylacetamide, and N-methylpyrrolidone.

[0017] Furthermore, the polyimide resin solution used for the self-adhesive surface layer in step 2) contains a toughening agent and a viscosity modifier, the toughening agent is a high temperature resistant thermoplastic polyimide resin with a concentration of 5 to 20 wt%; the viscosity modifier is one or more of a high temperature resistant unimidized thermosetting polyimide and a high temperature resistant PMR resin with a concentration of 5 to 10 wt%.

[0018] Furthermore, the stirring conditions of steps 1) and 2) are: mechanical stirring for 60 to 240 minutes at a temperature 30 to 60° C. lower than the boiling point of the solvent.

[0019] Furthermore, the two polyimide resin solutions obtained in steps 1) and 2) have a solid content of 20% to 50%, and a melt viscosity of 20 to 100 Pa·s at 50°C.

[0020] Furthermore, in step 3), the distillation temperature is 50-100° C. and the distillation time is 0.5-5 h.

[0021] Furthermore, in step 3), the solid content of the semi-solid polyimide prepreg used for impregnating the fibers is 75-90%, and the gel time of the glue at 120° C. is 10-15 minutes.

[0022] Furthermore, in step 3), the solid content of the semi-solid polyimide prepreg used for the self-adhesive surface layer is 65-75%, and the gel time of the glue at 120° C. is 10-15 minutes.

[0023] Furthermore, in step 4), the fiber cloth accounts for 50-75wt% of the total weight of the impregnated fiber prepreg, and the impregnated fiber resin film accounts for 20-40wt% of the total weight of the impregnated fiber prepreg.

[0024] Furthermore, in step 4), the fiber cloth is selected from one of high modulus carbon fiber (such as T300, T700, T800, T1000, T1100, etc.), high-strength glass fiber, aramid fiber, quartz fiber, and ultra-high molecular weight polyethylene fiber, and the fiber form is unidirectional or plain weave.

[0025] Furthermore, in step 4), the heating melting temperature of the semi-solid polyimide prepreg used for impregnating the fiber is 50-80°C, the coating speed is 2-6 m / min, the thickness of the single-layer impregnated fiber resin film is 0.05-0.2 mm, the composite temperature of the fiber cloth and the impregnated fiber resin film is 60-90°C, the composite pressure is 0.2-0.4 MPa, and the cooling table temperature of the hot pressing roller is 5-10°C.

[0026] Furthermore, the viscosity of the fiber impregnated resin film in step 4) is 12 to 400 Pa·s.

[0027] Furthermore, in step 5), the self-adhesive surface resin film accounts for 5-20wt% of the total weight of the fiber prepreg.

[0028] Furthermore, in step 5), the heating melting temperature of the semi-solid polyimide prepreg used for the self-adhesive surface layer is 50-80° C., the coating speed is 2-6 m / min, and the thickness of the single-layer film is 0.05-0.2 mm.

[0029] Furthermore, in the step 5), the composite temperature of the self-adhesive surface resin film and the impregnated fiber prepreg is 60-90°C, the composite pressure is 0.2-0.4Mpa, and the cooling stage temperature is 5-10°C.

[0030] Furthermore, the polyimide hot-melt prepreg obtained in step 6) is vacuum-packed in one of PE, PA, PET or aluminum foil fresh-keeping bags and stored in a refrigerator at low temperature.

[0031] In a second aspect, the present invention provides a polyimide hot-melt prepreg prepared by the above method.

[0032] In a third aspect, the present invention further provides a polyimide thermal composite material, which is prepared by the following steps:

[0033] The polyimide hot melt prepreg is softened by spraying a solvent on its surface, layered according to design requirements, and then heated and cured to obtain a polyimide thermal composite material.

[0034] Furthermore, the softening solvent is one or more of ethanol, methanol, petroleum ether, dichloromethane, dichloroethane, and tetrahydrofuran.

[0035] The present invention improves the dissolution and concentration process scheme, uses a double-layer impregnation gradient prepreg technology, adjusts the composite temperature and pressure of the imidized resin matrix and the reinforcing fiber, and realizes the gradient distribution of the properties such as the viscosity and solid content of the resin system on the cross section of the prepreg; firstly, the reinforcing fiber is fully impregnated with a resin system with high resin content and good softness, and then a toughening and viscosity-enhancing resin layer is composited on the surface of the reinforcing fiber after impregnation, so as to obtain an imidized polyimide hot-melt prepreg with controllable resin content and good paving adhesion, and then the impregnated preform is prepared by processes such as compression molding to obtain a high-quality fiber-reinforced composite material with low porosity, and the difficulty of controlling the molding process is greatly reduced, thereby improving production efficiency.

[0036] The beneficial effects of the present invention compared with the prior art are as follows:

[0037] (1) Compared with the conventional wet process using PMR polyimide resin solution, the present invention directly coats the resin into a film by hot melt method and then impregnates it with fibers to prepare prepreg, completely eliminating the multiple impregnation and cumbersome drying and solvent removal steps. This not only greatly simplifies the continuous preparation process of prepreg, but also significantly shortens the preparation cycle. At the same time, it avoids the fiber buckling phenomenon that is prone to occur in the wet process, effectively reduces the porosity of the composite material, and improves the molding quality of the final product.

[0038] (2) The present invention achieves precise control of the solid content of the polyimide prepreg, ensuring that the solvent content is maintained in an extremely low range of 5 to 20wt%. In addition, the effective volatilization of the solvent in the hot melt stage further reduces the solvent residue in the prepreg. This not only greatly reduces the release of volatile small molecules in the subsequent composite material molding process and reduces the potential impact on the environment, but also ensures that the prepreg is easy to lay and bond between layers while maintaining appropriate viscosity, laying a solid foundation for achieving low porosity, low defects, and high-quality molding and processing of large-sized or special-shaped composite parts.

[0039] (3) The prepreg of the present invention adopts a unique double-layer gradient impregnation structure. By constructing a layer of self-adhesive high-toughness resin film layer on the surface of the prepreg, it not only significantly improves the draping process of the prepreg, but also makes the paving operation more efficient and convenient, thereby effectively reducing the overall manufacturing cost of the composite material. In addition, the self-adhesive layer also plays a positive role in interlayer toughening, and synergizes with the internal impregnation layer resin matrix to give the composite material more excellent comprehensive mechanical properties, including but not limited to strength, toughness and fatigue resistance, further broadening its application field and market prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] Figure 1 This is a schematic diagram of the cross-sectional structure of a polyimide hot-melt prepreg proposed by the present invention.

[0041] Figure 2This is a comparison chart of the porosity of the composite materials in Example 1 and Comparative Example 1. DETAILED DESCRIPTION

[0042] In order to make the various technical features and advantages or technical effects in the above technical solutions of the present invention more obvious and easy to understand, the following is a detailed description with reference to embodiments and drawings.

[0043] In the following examples, various processes and methods not described in detail are conventional methods known in the art. Unless otherwise specified, the materials, reagents, devices, instruments, equipment, etc. used in the following examples can be obtained from commercial sources.

[0044] Example 1

[0045] (1) In a reaction vessel equipped with a heating and mechanical stirring device, polyimide NPI-550-2 / DMAc (mass ratio of 30 / 50) was added, the temperature was raised to 140° C., and stirred for 80 min to obtain a uniform solution, thereby obtaining a polyimide resin solution for impregnating fibers;

[0046] (2) In a reaction vessel equipped with a heating and mechanical stirring device, polyimide NPI-550-2 / Vespel toughening agent / viscosity modifier / DMF / dioxane (mass ratio of 30 / 8 / 5 / 30 / 30) was added, the temperature was raised to 100° C., and stirred for 80 min to obtain a uniform solution, thereby obtaining a polyimide resin solution for a self-adhesive surface layer;

[0047] (3) placing the resin solutions obtained in steps (1) and (2) in a vacuum distillation apparatus respectively, setting the temperature to 60° C. and the time to 5 h, respectively obtaining an impregnation polyimide prepreg with a solid content of 85% (the gel time of the glue solution at 120° C. is 12 min) and a self-adhesive surface polyimide prepreg with a solid content of 70% (the gel time of the glue solution at 120° C. is 13 min), collecting them with aluminum foil and sealing them at -18° C. for freezing and storage;

[0048] (4) The frozen impregnated resin was taken out and placed in a hot melt three-roller machine for hot melting at 70°C. The film speed was 4m / min. The thickness of the single-layer impregnated fiber resin film was 0.15mm. It was coated on the release paper to obtain a resin film (viscosity 150Pa.s). Then, the unidirectional T800 grade carbon fiber was compounded with the impregnated resin film, and a pressure of 0.3MPa was applied by a pressure roller at 75°C to obtain an impregnated prepreg. The cooling stage temperature of the hot pressing roller was 8°C.

[0049] (5) The heating and melting temperature of the self-adhesive layer polyimide prepreg is set to 750°C, the coating speed is 4.0 m / min, and the thickness of the single layer film is 0.15 mm, and the surface self-adhesive resin film (viscosity 120 Pa.s) is prepared, and the impregnated T800 continuous unidirectional carbon fiber of step (4) is double-sidedly laminated at a laminating temperature of 70°C to obtain a fiber prepreg. After being processed by a heating plate, a hot pressing roller, and a cooling plate, the upper release paper is peeled off and covered with a PE film to obtain a polyimide hot melt prepreg, namely, a T800 carbon fiber prepreg.

[0050] (6) The T800 carbon fiber prepreg was cut into appropriate sizes, stacked in the design direction and placed in a mold. After gradient heating to 335°C, it was thermally cured at a pressure of 2.2 MPa for 3 h, and then the pressure was maintained and the temperature was lowered. The mold was opened to obtain a fiber-reinforced composite material.

[0051] Example 2

[0052] (1) In a reaction vessel equipped with a heating and mechanical stirring device, polyimide NPI-550-2 / DMAc (mass ratio of 35 / 60) was added, the temperature was raised to 140° C., and stirred for 60 minutes to obtain a uniform solution, thereby obtaining a polyimide resin solution for impregnating fibers;

[0053] (2) In a reaction vessel equipped with a heating and mechanical stirring device, polyimide NPI-550-2 / polyimide toughening agent / PMR-350 / DMAc / dioxane (mass ratio of 30 / 10 / 8 / 30 / 50) was added, the temperature was raised to 120° C., and stirred for 60 min to obtain a uniform solution, thereby obtaining a polyimide resin solution for a self-adhesive surface layer;

[0054] (3) placing the resin solutions obtained in steps (1) and (2) in a vacuum distillation apparatus respectively, setting the temperature to 100° C. and the time to 0.5 h, respectively obtaining a 75% solid content impregnation polyimide prepreg (the gel time of the glue solution at 120° C. is 15 min) and a 65% solid content self-adhesive surface polyimide prepreg (the gel time of the glue solution at 120° C. is 15 min), collecting with aluminum foil and sealing and storing at -18° C.;

[0055] (4) The impregnated resin after freezing was taken out and placed in a hot melt three-roller machine for hot melting at 50°C. The coating speed was 2m / min, and the thickness of a single layer of impregnated fiber resin film was 0.2mm. The film was coated on release paper to obtain a resin film (viscosity 400Pa·s). The quartz fiber cloth was then composited with the impregnated resin film, and a pressure of 0.4MPa was applied by a pressure roller at 60°C to obtain an impregnated prepreg. The cooling stage temperature of the hot press roller was 10°C.

[0056] (5) The heating and melting temperature of the self-adhesive layer polyimide prepreg is set to 50°C, the coating speed is 2m / min, and the thickness of the single layer film is 0.2mm, and the surface self-adhesive resin film (viscosity 15Pa·s) is prepared, and double-sidedly laminated with the resin-impregnated quartz fiber cloth of step (4) at a laminating temperature of 50°C to obtain a fiber prepreg. After being processed by a heating plate, a hot pressing roller, and a cooling plate, the upper release paper is peeled off and covered with a PE film to obtain a polyimide hot-melt prepreg, i.e., a quartz fiber cloth prepreg.

[0057] (6) The quartz fiber cloth prepreg is cut into suitable sizes, laid out in the design direction and placed in a mold. After the temperature is gradually increased to 320°C, it is thermally cured at a pressure of 2 MPa for 3.5 h, and then the temperature is reduced while maintaining the pressure, and the mold is opened to obtain a fiber-reinforced composite material.

[0058] Example 3

[0059] (1) In a reaction vessel equipped with a heating and mechanical stirring device, polyimide KH-360 / DMAc (mass ratio of 30 / 50) was added, the temperature was raised to 120° C., and stirred for 240 min to obtain a uniform solution, thereby obtaining a polyimide resin solution for impregnating fibers;

[0060] (2) In a reaction vessel equipped with a heating and mechanical stirring device, polyimide NPI-550-2 / polyimide toughening agent / PMR-370 / DMAc / n-butanol (mass ratio of 30 / 10 / 8 / 30 / 50) were added, the temperature was raised to 80° C., and stirred for 240 min to obtain a uniform solution, thereby obtaining a polyimide resin solution for a self-adhesive surface layer;

[0061] (3) placing the resin solutions obtained in steps (1) and (2) in a vacuum distillation apparatus, respectively, setting the temperature to 80° C. and the time to 2.5 h, to obtain a 90% solid content (the gel time of the glue solution at 120° C. is 10 min) impregnation polyimide prepreg and a 75% solid content self-adhesive surface polyimide prepreg (the gel time of the glue solution at 120° C. is 10 min), respectively, collecting and sealing with aluminum foil and storing at -18° C.;

[0062] (4) Take out the frozen impregnated resin, place it in a hot melt three-roller machine and heat-melt it at 80°C. The coating speed is 6m / min. The thickness of the single-layer impregnated fiber resin film is 0.1mm. Apply it on the release paper to obtain a resin film (viscosity 12Pa·s). Then, the T700 carbon fiber is compounded with the impregnated resin film, and a pressure of 0.2MPa is applied by a pressure roller at 90°C to obtain an impregnated prepreg. The cooling stage temperature of the hot press roller is 5°C.

[0063] (5) The heating and melting temperature of the self-adhesive layer polyimide prepreg is set to 80°C, the coating speed is 3.0 m / min, and the thickness of the single layer film is 0.10 mm, and the surface self-adhesive resin film (viscosity 12 Pa·s) is prepared, and the surface is double-sidedly laminated with the resin-impregnated T700 carbon fiber of step (4) at a laminating temperature of 90°C to obtain a fiber prepreg. After being treated with a heating plate, a hot pressing roller, and a cooling plate, the upper release paper is peeled off and covered with a PE film to obtain a polyimide hot-melt prepreg, namely, a T700 carbon fiber prepreg.

[0064] (6) The T700 carbon fiber prepreg was cut into appropriate sizes, stacked in the design direction and placed in a mold. After the temperature was gradually increased to 330°C, it was thermally cured at a pressure of 5.0 MPa for 3 h, and then the pressure was maintained and the temperature was lowered. The mold was opened to obtain a fiber-reinforced composite material.

[0065] Comparative Example 1

[0066] The selected material system and process are the same as those in Example 1, except that:

[0067] (1) In the prepreg preparation process, no self-adhesive surface resin prepreg was prepared, and the prepreg had no self-adhesive surface resin film. Other process parameters were the same as those in Example 1.

[0068] (2) In the composite material preparation process, the solvent was not sprayed on the surface of the polyimide carbon fiber prepreg to soften it. The molding and curing process was the same as in Example 1.

[0069] The properties of the polyimide resin for prepreg and the hot-melt prepreg of the above-mentioned embodiments and comparative examples are shown in Table 1, and the interlaminar shear and porosity of the prepared composite materials are shown in Table 2.

[0070] Table 1 Summary of properties of polyimide resin and hot melt prepreg

[0071]

[0072] * Prepreg viscosity, resin content and volatile matter are measured according to standards HB7736.3-2004, HB7736.5-2004 and HB7736.4-2004 respectively.

[0073] Table 2 Summary of properties of polyimide composite materials

[0074]

[0075] *Porosity is measured according to GB / T3365-2008, interlaminar shear strength is measured according to JC / T773-1996

[0076] It can be seen from the data in Table 1 and Table 2 that, compared with Comparative Example 1, the prepregs of Examples 1-3 have good viscosity, controllable resin content and volatile matter, and meet the process parameter requirements of hot-melt prepreg lamination. The obtained polyimide composite materials have high fiber alignment, no obvious internal defects, a porosity of less than 1%, and a unidirectional fiber interlayer shear strength of 112 MPa (Example 1), which is significantly higher than Comparative Example 1, showing excellent internal quality and mechanical properties.

[0077] Figure 2 1 is a comparison of the internal quality photos of the composite material C in Example 1 and Comparative Example 1. Figure 2 It can be seen that the composite material obtained in Example 1 has no defects such as looseness and delamination, and has a smooth surface and good internal quality. However, in Comparative Example 1, the composite material has obvious looseness and delamination, fiber buckling, uneven thickness, and poor internal quality. This shows that under the same curing conditions, the prepreg in Comparative Example 1 has a low glue content and poor draping properties, which is not conducive to the preparation of high-quality composite materials.

[0078] Although the present invention has been disclosed as above by way of embodiments, it is not intended to limit the present invention. Appropriate modifications or equivalent substitutions of the technical solutions of the present invention made by ordinary technicians in the field should all be included in the protection scope of the present invention. The protection scope of the present invention shall be based on what is defined in the claims.

Claims

1. A method for preparing a polyimide hot-melt prepreg, characterized in that the steps include: 1) mechanically stirring polyimide and a single solvent to obtain a polyimide resin solution for impregnating fibers; 2) mechanically stirring the polyimide and the mixed solvent to obtain a polyimide resin solution for the self-adhesive surface layer; 3) performing reduced pressure distillation on the two polyimide resin solutions obtained in steps 1) and 2) to obtain a semi-solid polyimide prepreg for impregnating the fiber and for surface self-adhesion; 4) placing the semi-solid polyimide prepreg for impregnating the fiber in a hot melt three-roller machine for hot melting, coating the prepreg on a release paper to obtain an impregnated fiber resin film, and compounding the impregnated fiber resin film with a fiber cloth through multiple hot pressing rollers to obtain an impregnated fiber prepreg; 5) placing the semi-solid polyimide prepreg for the self-adhesive surface layer in a hot melt three-roller machine for hot melting, and coating it on a release paper to obtain a self-adhesive surface resin film; the self-adhesive surface resin film is double-sidedly laminated with the fiber cloth impregnated with the fiber prepreg obtained in step 4) through multiple hot pressing rollers to obtain a fiber prepreg; 6) The fiber prepreg obtained in step 5) is processed by a heating plate, a hot pressing roller, and a cooling plate, the upper release paper is peeled off and covered with a PE film to obtain a polyimide hot-melt prepreg.

2. The method according to claim 1, characterized in that The polyimide in steps 1) and 2) is an acetylene-terminated, allyl norbornene-terminated or phenylacetylene-terminated polyimide resin; the single solvent in step 1) is selected from one of N,N-dimethylacetamide, dimethylformamide and N-methylpyrrolidone; the mixed solvent in step 2) includes a low boiling point solvent and a high boiling point solvent, the low boiling point solvent is selected from one or more of dioxane, n-butanol, isopropanol, cyclopentanone and sec-butanol, and the high boiling point solvent is selected from one or more of N,N-dimethylformamide, N,N-dimethylacetamide and N-methylpyrrolidone.

3. The method according to claim 1, characterized in that The polyimide resin solution used for the self-adhesive surface layer in step 2) contains a toughening agent and a viscosity modifier, wherein the toughening agent is a high temperature resistant thermoplastic polyimide resin with a concentration of 5 to 20 wt %; the viscosity modifier is one or more of a high temperature resistant unimidized thermosetting polyimide and a high temperature resistant PMR resin with a concentration of 5 to 10 wt %.

4. The method according to claim 1, characterized in that The stirring conditions of steps 1) and 2) are: mechanical stirring for 60 to 240 minutes at a temperature 30 to 60° C. lower than the boiling point of the solvent; the solid content of the two polyimide resin solutions obtained is 20% to 50%, and the melt viscosity at 50° C. is 20 to 100 Pa·s.

5. The method according to claim 1, characterized in that In step 3), the distillation temperature is 50-100°C and the time is 0.5-5h; the solid content of the semi-solid polyimide prepreg used for impregnating the fiber is 75-90%, and the gel time of the glue at 120°C is 10-15min; the solid content of the semi-solid polyimide prepreg used for the self-adhesive surface layer is 65-75%, and the gel time of the glue at 120°C is 10-15min.

6. The method according to claim 1, characterized in that In step 4), the fiber cloth is selected from one of high modulus carbon fiber, high strength glass fiber, aramid fiber, quartz fiber, and ultra-high molecular weight polyethylene fiber, and the fiber form is unidirectional or plain weave fabric; the fiber cloth accounts for 50-75wt% of the total weight of the impregnated fiber prepreg, and the impregnated fiber resin film accounts for 20-40wt% of the total weight of the impregnated fiber prepreg.

7. The method according to claim 1, characterized in that In step 4), the heating melting temperature of the semi-solid polyimide prepreg used for impregnating the fiber is 50-80°C, the coating speed is 2-6 m / min, the thickness of the single-layer impregnated fiber resin film is 0.05-0.2 mm, the composite temperature of the fiber cloth and the impregnated fiber resin film is 60-90°C, the composite pressure is 0.2-0.4 MPa, and the cooling table temperature of the hot pressing roller is 5-10°C.

8. The method according to claim 1, characterized in that In step 5), the self-adhesive surface resin film accounts for 5 to 20 wt% of the total weight of the fiber prepreg; the heating and melting temperature of the semi-solid polyimide prepreg used for the self-adhesive surface is 50 to 80°C, the coating speed is 2 to 6 m / min, and the thickness of the single layer film is 0.05 to 0.2 mm; the composite temperature of the self-adhesive surface resin film and the impregnated fiber prepreg is 60 to 90°C, the composite pressure is 0.2 to 0.4 MPa, and the cooling table temperature is 5 to 10°C.

9. A polyimide hot melt prepreg, characterized in that: Prepared by the method according to any one of claims 1 to 8.

10. A polyimide thermal composite material, characterized in that: Prepared by the following steps: The polyimide hot melt prepreg prepared by the method according to any one of claims 1 to 8 is softened by spraying a solvent on its surface, layered according to design requirements, and then heated and cured to obtain a polyimide thermal composite material; the softening solvent is one or more of ethanol, methanol, petroleum ether, dichloromethane, dichloroethane, and tetrahydrofuran.

Citation Information

Patent Citations

  • Polyimide resin as well as preparation method and application thereof

    CN102604092A

  • Polyimide fiber bismaleimide resin composite and preparation method thereof

    CN106009668A

  • Method for improving heat oxidation stability of RTM formed polyimide composite material

    CN110588022A

  • Non-PMR type polyimide carbon fiber prepreg, composite material and preparation method thereof

    CN112694749A

  • Preparation method of benzoxazine prepreg by hot melting method

    CN114230832A

Cited By

  • High-toughness high-temperature curing epoxy resin prepreg for automatic fiber placement and preparation method of high-toughness high-temperature curing epoxy resin prepreg

    CN120606583A

  • Fiber-reinforced thermoplastic polyimide laminated board as well as preparation method and application thereof

    CN122165725A